Cardiac stem cell aging and heart failure. (January 2018) - Cesselli, Daniela; Aleksova, Aneta; Mazzega, Elisa; Caragnano, Angela; Beltrami, Antonio Paolo
Graphical abstract: Abstract: A side effect of the medical improvements of the last centuries is the progressive aging of the world population, which is estimated to reach the impressive number of 2 billion people with more than 65 years by 2050. As a consequence, age-related diseases, such as heart failure, will affect more and more patients in the next years. To understand the biological bases of these diseases will be a crucial task in order to find better treatments, and possibly slow age-related morbidity and mortality. Cardiac stem cells have been at the center of a heated debate and their potential involvement in cardiac homeostasis has been questioned. In this review, we summarize evidence obtained by independent groups, on different animal models and humans, that strongly support the important role played by immature, cardiac resident cells in the cardioprotection against heart failure.